Peran Public Relations Pada Program CSR Dalam Rangka Meningkatkan Citra Positif - Maharani Imran; Maharani Imran (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2008)
In the last decade, company believed their Public Relations to manage the Corporate Social Responsibility (CSR) Program. CSR held in order to strengthen the sustainability of the company in a region, by building cooperation among stakelmlders by arranging community relations programs. The aim of this research is to find out about how the role of public relations in enhancing the positive image of the company in the CSR program. The research used a liturature studies and shows that CSR activities can enhance the positive image of companies by using the stages in the process of public relations, they are fact finding, problem mapping planning and programming, action and communication, and evaluation. Company should make sustainable CSR program that have positive impact to society, both in economically, environmentally, and socially.